РЕГИОНАЛЬНЫЕ ПРИОРИТЕТЫ ВНЕШНЕЭКОНОМИЧЕСКОЙ ДЕЯТЕЛЬНОСТИ КАЗАХСТАНА (Journal of Economic Research & Business Administration, 2015)
In article problems of interaction of Kazakhstan within the limits of regional integration associations are considered. The attention to necessity of maintenance of effective integration within the limits of integration communities as factor of steady economic development of national economy is thus focused. In article perspective directions of development of foreign trade of republic the next years are defined.